Marine inspired biomaterials: from sea up to tissue regeneration approaches - Silva, Tiago H. (2014)
Introduction Nature has been since ever the inspiration driving mankind for the development of amazing systems, materials, constructions, devices, etc. Marine environment is not exception and the technological developments allowing the access to deeper locations and organisms are opening even more that gate to a new dimension of knowledge. One of the fields where marine organisms are acting stimulating the imagination of mankind is health, fostering the development of innovative pharmaceuticals and cosmetics, as well as new biomedical systems [1]. In this presentation, the authors will address the efforts that are being made by 3B’s Research Group on the development of marine inspired biomaterials towards tissue regeneration. Materials and Methods Polymer extraction Collagen has been extracted from several fish skins by acetic acid extraction, complemented by enzymatic treatment by using pepsin. Polysaccharides have been extracted from different marine sources, namely from algae (sulfated polysaccharides, typically using hot water and precipitation with organic solvents) and from squid pens (chitin, further converted into chitosan, by NaHO treatments). Development of biomaterials Porous structures have been developed following different processing techniques, from freeze-drying (chitosan and collagen) to particle agglomeration (chitosan and composites with nanohydroxiapatite) and rapid prototyping (carrageenans). Their morphological properties were assessed by SEM and micro-computed tomography (μCT); mechanical properties evaluated by compression tests; biological performance has been tested with chondrocyte-like cell line ATDC5 (chitosan and collagen scaffolds) or adipose derived stem cells, ASCs (chitosan scaffolds). Additionally, natural collagenous porous structures were obtained by decellularization of marine sponges, together with extraction of toxic compounds. Results Several marine origin polymers were used to produce porous structures envisaged as scaffolds for tissue engineering approaches. Squid chitosan scaffolds were produced by freeze-drying, in which ATDC5 cells adhered and proliferated. Squid chitosan scaffolds were produced also by particle aggregation, including as composites with nanohydroxiapatite, in which ASCs were successfully cultured up to 7 days. Carrageenan structures were produced by rapid prototyping, revealing to be non-cytotoxic to rat lung fibroblasts. Marine collagen structures have been produced by freeze-drying and crosslinked with genipin under dense CO2, obtaining porous structures stable in culture medium, in which ATDC5 cells were successfully cultured. Additionally, the collagenous structure of marine sponges was also assessed as nature made scaffolds, revealing a non toxic structure able to support culture of osteoblast-like cell line. Discussion and Conclusions Several porous structures have been produced based on marine origin polymers, and successfully used as 3D support for cell culture. Their use as scaffolds is enhancing the potential of marine resources and inspiration for tissue regeneration approaches. References 1. TH Silva,…, RL Reis, Int Mater Rev 57 (2012) 276-306. Acknowledgments Funding is acknowledged from projects IBEROMARE (POCTEP), MARMED (Atlantic Area), NOVOMAR (POCTEP), POLARIS (FP7) and SPECIAL (FP7).